The Maternal Cytokine and Chemokine Profile of Naturally Conceived Gestations Is Mainly Preserved during In Vitro Fertilization and Egg Donation Pregnancies - Alicia Martínez-Varea; Begoña Pellicer; Vicente Serra; David Hervás-Marín; Alicia Martínez-Romero; José Bellver; Alfredo Perales-Marín; Antonio Pellicer (Journal of Immunology Research)
This prospective longitudinal study aimed at comparing maternal immune response among naturally conceived (NC; n=25), in vitro fertilization (IVF; n=25), and egg donation (ED; n=25) pregnancies. The main outcome measures were, firstly, to follow up plasma levels of interleukin (IL) 1beta, IL2, IL4, IL5, IL6, IL8, IL10, IL17, interferon gamma, tumor necrosis factor-alpha (TNFα), transforming growth factor-beta (TGFβ), regulated upon activation normal T-cell expressed and secreted (RANTES), stromal cell-derived factor 1 alpha (SDF1α), and decidual granulocyte-macrophage colony-stimulating factor (GM-CSF) during the three trimesters of pregnancy during the three trimesters of pregnancy; secondly, to evaluate if the cytokine and chemokine pattern of ED pregnant women differs from that of those with autologous oocytes and, thirdly, to assess if women with preeclampsia show different cytokine and chemokine profile throughout pregnancy versus women with uneventful pregnancies. Pregnant women in the three study groups displayed similar cytokine and chemokine pattern throughout pregnancy. The levels of all quantified cytokines and chemokines, except RANTES, TNFα, IL8, TGFβ, and SDF1α, rose in the second trimester compared with the first, and these higher values remained in the third trimester. ED pregnancies showed lower SDF1α levels in the third trimester compared with NC and IVF pregnancies. Patients who developed preeclampsia displayed higher SDF1α plasma levels in the third trimester.